Prediction of Adult Criminal Careers from Early Delinquency Offense Characteristics in the 1958 Philadelphia Birth Cohort - D. M. Carkin; P. E. Tracy (Russian Journal of Economics and Law)
Objective: to investigate the impact of delinquency conduct on adult criminal career (by the example of delinquent boys in the 1958 Philadelphia Birth Cohort).Methods: dialectical approach to cognition of social phenomena, allowing to analyze them in historical development and functioning in the context of the totality of objective and subjective factors, predetermined the following research methods: formal-logical, comparative-legal, and sociological.Results: by the example of delinquent boys in the 1958 Philadelphia Birth Cohort, the authors investigate the nature of delinquency conduct, offense-by-offense, and its relationship to adult crime status. Although it is convenient to think of an offender's delinquency career as a whole, such a career actually consists of one or more specific offenses, and offense conduct can be worth studying in its own right. Thus, it is necessary to determine whether the timing, type, severity, court disposition, and so on of these juvenile offenses can be used to predict adult career pathways. An extensive review of the literature revealed that investigations of early offense conduct and its connection to adult crime are exceedingly scarce. Scientific novelty: for the first time, the research proves that the facility disposition appears to have a criminogenic effect. The juvenile court dispositions are significantly predictive of the adult paths-the less severe the disposition, the less adult crime. At the time of the second offense, age is found significant in that the younger the individual is at the time of the second offense, the greater the chances are that the individual will receive a higher score in the adult path variable. The younger the individual is at the time of the third offense, the more likely he is to score higher in the adult paths. Thus, to decrease the adult crime rates, it is necessary to work with delinquent criminals before they commit their third crime. Besides, it is substantiated that the strongest predictor of adult crime status was juvenile court dispositions. Practical significance: the main provisions and conclusions of the article can be used in research and teaching for the consideration of the issues related to the influence of juvenile offenses on the adult criminal career.